Legal Review of Inpatient Services for Five Diagnoses (Typhoid, Dyspepsia, Gastroenteritis, Febricular Observation and Dengue Fever) for National Health Insurance Participants at Primary Level Health Care Facilities - Kristina, Khaterina; Sagala, Parluhutan; Suhadi, Suhadi (Journal of Community Health Provision, 2024)
The national health insurance promulgated in the National Social Security System (SJSN) law in 2014 is an implementation of SJSN. Based on BPJS Health data from 2017 to 2019, Thypus, Dyspepsia, Gastroenteritis, Febrile Observation and Dengue Fever which are 5 (five) non-specialist diagnoses are included in the 10 (ten) diagnoses absorbing the largest costs and the most diagnoses in Advanced Inpatient (RITL) where the results of secondary data analysis of data amounted to 39% during 2017 – 2019 from all reference data with Severity Level light. In the study, the research method used is through the normative juridical method approach. The results of the discussion explained that primary health care in the JKN program is tasked with managing cases from 144 diagnoses. The capacity of inpatient services at FKTP is the main key in completing the diagnosis of Typhoid, Dyspepsia, Gastroenteritis, Febrile Observation and Dengue Fever, and this is formed from the competence of human resources owned, availability of facilities.